Estimation of the Surface Properties of Unmodifed and Strongly Oxidized Active Carbons on the Basis of Water Vapour Adsorption Isotherms - J. Choma; M. Jaroniec (Adsorption Science & Technology)
Water vapour adsorption isotherms were measured for a series of commercial active carbons and one carbon black oxidized with concentrated nitric acid at its boiling temperature. A comparative analysis of the surface properties of the unmodified and strongly oxidized active carbons was performed on the basis of the adsorption potential distributions (APDs) calculated from these adsorption isotherms. It was shown that the APDs for oxidized carbons exhibit some extra details (e.g., peaks) in the range of high adsorption potentials which can be assigned to interactions of water molecules with oxygen surface groups formed during the oxidation process. This is especially visible for oxidized carbon black. The observed sensitivity of the APDs obtained from water vapour adsorption isotherms make them attractive functions for monitoring the surface changes in active carbons due to their oxidation.